PENGARUH PENGGUNAAN INFORMASI AKUNTANSI MANAJEMEN, MODAL USAHA DAN KEPRIBADIAN WIRAUSAHA TERHADAP KINERJA MANAJERIAL (Studi Kasus Pada UMKM Batik Tulis Lasem Se-Kabupaten Rembang) - Maslikah, Maslikah; Alliyah, Siti; Azizi, Zakky Wahyuddin (JAB (Jurnal Akuntansi & Bisnis), 2018)
This study uses independent variables The Use of Management Accounting Information (X1), Business Capital (X2) and Entrepreneurial Personality (X3), and the dependent variable Managerial Performance (Y), aims to prove the effect of using management accounting information, business capital and entrepreneurial personality on performance managerial. Variable measurement technique uses a Likert scale. The data used are primary data, namely a data based on a questionnaire and the results of answers from respondents. While the analysis used is multiple linear regression analysis which is processed with SPSS 19 to find out how the influence of the use of management accounting information, business capital and entrepreneurial personality on managerial performance. The sample used in this study was taken from UMKM Batik Tulis Lasem Se-Kabupaten Rembang. With the number of 120 respondents obtained by saturated sample techniques.The results showed that the variable use of management accounting information had a significant positive effect on managerial performance, the business capital variable had a non-significant negative effect on managerial performance and the entrepreneurial personality had no significant positive effect on managerial performance. Adjusted R2 research value is 0.056, which means that the effect of using management accounting information, business capital and entrepreneurial personality on managerial performance is 5.6%, while the remaining 94.4% is influenced by other factors outside the research variable. Keywords : Management Accounting Information, Business Capital, Personality                      Entrepreneurship, Managerial Performance.